Immune reconstitution inflammatory syndrome-associated disseminated Kaposi's sarcoma in a patient infected with human immunodeficiency virus: Report of an autopsy case - Chiu-Hsuan Cheng; Yung-Hsiang Hsu (Tzu Chi Medical Journal)
Immune reconstitution inflammatory syndrome is a collection of inflammatory disorders associated with paradoxical worsening of preexisting infectious processes following the initiation of highly active antiretroviral therapy (HAART) in individuals infected with human immunodeficiency virus (HIV). It involves a wide range of pathogens, neoplasms such as Kaposi's sarcoma (KS) and some autoimmune diseases. We describe an autopsy report of a 40-year-old man infected with HIV. He experienced a rapid dissemination of KS resulting in death within 6 months after starting HAART. His serum viral load had significantly decreased 4 log10 within 32 days and his CD4+ T-cell count increased 4-fold. He presented with multiple skin lesions over the chin and anterior neck, which rapidly spread over the trunk, 4 extremities, perianal region, and penis. Finally, he developed acute dyspnea and a plain chest radiograph showed bilateral pulmonary infiltrations. Despite treatment, he died of acute respiratory failure. At autopsy, multiple KS lesions were noted in the bilateral lungs, liver, kidneys, and gastrointestinal tract. Increased inflammatory cytokines during immune reconstruction from HAART-reactive human herpes virus type-8 infection, linked to the tumorigenesis of KS, finally led to rapid dissemination and death.